Allie Finkle's Rules for Girls: moving day - Cabot, Meg. (New York Scholastic Press, 2008)
Nine-year-old Allie Finkle has rules for everything and is even writing her own rule book, but her world is turned upside-down when she learns that her family is moving across town, which will mean a new house, school, best friend, and plenty of new rules.
Elementary
Keywords: Best friends - Fiction; Friendship - Fiction; Family life - Fiction; Schools - Fiction; Behavior - Fiction